The gloss and the text: William Perkins on interpreting Scripture with Scripture - Ballitch, Andrew S. (Studies in Historical and Systematic Theology, 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword -- Preface -- Abbreviations -- Chapter 1: Introduction -- Thesis -- History of Research -- Methodology -- Chapter 2: Perkins's Exegetical Method -- Biographical Context -- Hermeneutical Context -- Patristic Foundation -- Medieval Antecedents -- The Reformed Tradition -- Contemporary English Works -- Conclusion -- The Arte of Prophecying -- Biblical Authority -- Biblical Interpretation -- Conclusion -- Chapter 3: Exegesis in Sermons and Commentaries -- The True Gaine: Philippians 3:7-11 -- Galatians -- Context -- Collation -- Analogy of Faith -- Christ's Sermon on the Mount -- Interpretation of the Parts in the Context of the Whole -- Qualification in Light of the Canon -- The Combat Betweene Christ and the Devill: Matthew 4:1-11 -- Revelation 1-3 -- Exegesis of the Preface -- Exegesis of the Vision of Christ -- Exegesis of the Epistles -- A Cloud of Faithful Witnesses: Hebrews 11 -- Exegesis of the Description of Faith -- Exegesis of Preflood Exemplars -- Exegesis of the Patriarchs' Example -- Exegesis of Examples from Israelite National History -- Jude -- An Exhortation to Repentance: Zephaniah 2:1-2 -- Conclusion -- Chapter 4: Exegesis in Practical Works -- The Christian Life -- How to Live Well -- How to Die Well -- The True Manner of Knowing Christ Crucified -- Man's Natural Imaginations -- The Practice of Repentance -- The Government of the Tongue -- The Household -- Vocation -- Equity and Moderation -- Christian Ministry -- The Calling of the Ministry -- Early Work on Assurance -- The Greatest Case of Conscience -- A Discourse of Conscience -- A Graine of Musterd-Seede -- Cases of Conscience -- Conclusion -- Chapter 5: Exegesis in Theological Works -- Catechism -- The Foundation of Christian Religion -- The Lord's Prayer -- The Apostles' Creed -- Context -- Collation.